(untitled) (Journal of the College of Basic Education, 2023)
After the 1973 there are several Public Key cryptosystem are development, all system based on hard mathematical problems such as discrete logarithm, Integer Factorization, subnet, or elliptic curve Discrete Logarithm problem .Which problems are defined over finite a blain Group. In this paper we proposes new concept in the public key system that is depend on isomorphism a blain group (IAG), mainly Algorithm. Along this paper new functions were revealed that have difference in complexity to find its inverse due to the isomorphism group